Multicolor colorimetric detection of ochratoxin A via structure-switching aptamer and enzyme-induced metallization of gold nanorods. (1st August 2020) - Tian, Fengyu; Zhou, Jing; Fu, Ruijie; Cui, Yongliang; Zhao, Qiyang; Jiao, Bining; He, Yue
Highlights: A multicolor colorimetric assay for the high-resolution visual detection of ochratoxin A was proposed. This method was based on the structural switching of the aptamer and enzyme induced metallization of gold nanoroad. Grape juice sample analysis was easily performed with satisfied results. The linear range is from 12.5 to 20, 000 nM. A detection limit of 9.0 nM was obtained. Abstract: Colorimetric aptasensors have been intensively studied for the ochratoxin A (OTA) detection, but they mostly exhibit just one-color change, resulting in poor visual resolution and limited use for semi-quantitative analysis. Thus, we designed a high-resolution colorimetric assay on the basis of aptamer structural switching and enzyme-induced metallization of gold nanorods (AuNRs). DNA-alkaline phosphatase (ALP)-immobilized magnetic beads were prepared. The aptamer bounded to OTA to form G-quadruplexes, releasing ALP-labelled complementary DNA (cDNA-ALP). After magnetic separation, cDNA-ALP catalyzed the decomposition of ascorbic acid 2-phosphate to ascorbic acid that reduced Ag +, forming an Ag shell on the surface of AuNRs. This caused a blue-shift of the longitudinal local surface plasmon resonance peak of the AuNRs and a naked eye visible multicolor change. Under optimal conditions, the assay exhibited a 9.0 nM detection limit for OTA, with high specificity. This method is promising for the on-site visual semi-quantitative detection of mycotoxins in foods.